Surface Modification of Ca(NO3)2·4H2O Crystals with Epoxy Resins at Normal Temperature Through a Mechanical Dry Method - Liu, Dechun; Zhu, Jiahua (Asian Journal of Chemistry, 2013)
In order to solve problem of Ca(NO3)2·4H2O crystals easy deliquescence at normal temperature, the surface modification of Ca(NO3)2·4H2O crystals with epoxy resins by a mechanical dry encapsulation process taken diethylenetriamine as curing agent in ethanol was investigated through FTIR, TG/DTA, optical microscopy and moisture absorption performance test in atmosphere. The results showed that the curing time of the epoxy resin was shortened sharply with the increase of its concentration and the increase of the concentration of curing agent. The optimized formula for Ca(NO3)2·4H2O crystals coated is of epoxy resin, ethanol and diethylenetriamine at the mass ratio of 7:1:1.05. About 5-7 % weight of Ca(NO3)2·4H2O crystals for formula coating materials has the best effects. It is suggested that the moisture absorption growth rate of these separate white granules increased slowly and effectively avoided Ca(NO3)2·4H2O crystals deliquescent at normal temperature. Furthermore, the thermal stability of the materials was enhanced dramatically.